PEMBELAJARAN TARI JEPEN DAPAT MENINGKATKAN KECERDASAN KINESTETIK PADA ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN DARUSSAKINAH 02 TENGGARONG SEBERANG TAHUN AJARAN 2016 / 2017 - Arbibah - Arbibah; Mahkamah - Brantasari; Ratna - Khairunnisa (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
This study aims to improve students’ Kinestetik intelegence through basic movement of jepen dance,i.e : Butterfly dance for 5-6 year old in Darussakinah 02 Playgroup Tenggarong Seberang. Therefore, The researcher conducted a classroom actionresearch to improve the quality of achievenment. In each cycle, the researcher applied four stages; planning, implementation, observation, andreflection. In this study, the researcher employed two cycles with four meetings in each eycle. Moreover, the observed aspects in this study were coordination among body movement, eyes, hands, and legs, strength, agility and balance.  This research was conducted in Darussakinah 02 Playgroup Tenggarong Seberang on February 2017. The researcher involved ten 5-6 year old students of Darussakinah 02 Playgroup as the research subjects, consisting five males dan five femals. To gather the data, the researcher employed technique, documentation and performance test. Having analyzed the data, it is found that, in cycle 1, 50,7 % students were active in responding the lesson for preparing the basic movementof dance. Meanwhile, at cycle 2, 80,5 % students managed to do the dance movement. Considering the increasing percentage in cycle 2 compared with cycle 1, it can be said that student experienced progress. In brief, students’ kinesthetic intelligence was successfully improved through the implementation of Jepen Dance From Kutai, which has been recreated into Buterfly Jepen Dance and Performed in group.